A methodology for the analysis of the Rayleigh-wave ellipticity - V Corchete (Earth Sciences Research Journal, 2013)
In this paper, a comprehensive explanation of the analysis (filtering and inversion) of the Rayleigh-wave ellipticity is performed, and the use of this analysis to determine the local crustal structure beneath the recording station is described. This inversion problem and the necessary assumptions to solve are described in this paper, along with the methodology used to invert the Rayleigh-wave ellipticity. The results presented in this paper demostrate that the analysis (filtering and inversion) of the Rayleigh-wave ellipticity is a powerful tool, for studying the local structure of the crust beneath the recording station. Therefore, this type of analysis is very useful for studies of seismic risk and/or seismic design, because it provides local earth models in the range of crustal depths.